2016
DOI: 10.1002/cmdc.201600261
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Syntheses of Benzimidazole‐Containing Selenadiazole Derivatives That Induce Cell‐Cycle Arrest and Apoptosis in Human Breast Cancer Cells by Activation of the ROS/AKT Pathway

Abstract: The use of selenium-containing heterocyclic compounds as potent cancer chemopreventive and chemotherapeutic agents has been well documented by a large number of clinical studies. In this study we developed a new approach to synthesize four benzimidazole-containing selenadiazole derivatives (BSeDs). The method uses a combination of peptide coupling reagents and microwave irradiation. This strategy features milder reaction conditions, higher yields, and shorter reaction times. The synthetic BSeDs were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…A previous study has shown that ROS are capable of causing extensive damage to DNA, proteins, and lipids, and thus it is believed that ROS is tumorigenic by increasing genomic instability [15]. Basal levels of ROS are essential for cell physiologic function, whereas overflowing ROS formation induces apoptosis and cell cycle arrest in cancer [16, 17]. Previous studies have demonstrated that ROS induces ER stress-dependent apoptosis through depletion of calcium stores in the ER via inhibition of Ca 2+ -ATPase [18].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that ROS are capable of causing extensive damage to DNA, proteins, and lipids, and thus it is believed that ROS is tumorigenic by increasing genomic instability [15]. Basal levels of ROS are essential for cell physiologic function, whereas overflowing ROS formation induces apoptosis and cell cycle arrest in cancer [16, 17]. Previous studies have demonstrated that ROS induces ER stress-dependent apoptosis through depletion of calcium stores in the ER via inhibition of Ca 2+ -ATPase [18].…”
Section: Introductionmentioning
confidence: 99%
“…In most instances, tumor metastasis causes higher death rate than the primary tumor dose, and it has become a major cause of death in cancer treatment (Liang et al., 2016 ). Therefore, the suppression or prevention of metastatic diseases becomes especially important in the therapeutic process.…”
Section: Resultsmentioning
confidence: 99%
“…While in case of MIL treated parasite lower values were obtained (sub-G0/G1: 10.19%, S: 1.06%, and G2/M: 0.18%). These findings suggest that C1 arrests parasites in sub-G0/G1 phase and induces cell death resembling apoptosis [59][60][61][62][63] . We could also observe that approximately 8.69% treated parasite population was annexinV-positive and PI-negative (Fig.…”
Section: C1 Induces Sub-g0/g1 Phase Cell-division Arrest and Phosphatmentioning
confidence: 87%